Mapping the impact of home‐ and host‐country institutions on human resource management in emerging market multinational companies: A conceptual framework. (20th February 2019) - Edwards, Tony; Schnyder, Gerhard; Fortwengel, Johann
Abstract : While there is a growing literature concerned with multinational companies from emerging markets (EMNCs), it does not contain a robust conception of how institutions shape human resource (HR) practices in such firms. We contribute to filling this gap through developing a framework of how institutions create a range of constraints and opportunities for EMNCs. Specifically, our framework contains three key elements of how MNCs from emerging markets interact with institutions: EMNCs develop approaches that to some extent reflect the perceived strengths and weaknesses of the institutions in the home country ( institutional conditioning ); the strategies of actors in EMNCs can overcome the weaknesses of the home country by drawing on institutions in other countries ( institutional arbitrage ); and the actions of EMNCs can reinforce, or create pressures for change in, the institutional context in the countries in which they operate ( institutional change/consolidation ). By mapping this set of strategies of EMNCs, we contribute to a fuller understanding of the relationship between institutions and HR practices, and we outline how the rise of EMNCs reshapes the global landscape by adding new kinds of firm behavior to capitalist diversity.